Do biosurfactants as anti-biofilm agents have a future in industrial water systems? - Jimoh, Abdullahi Adekilekun; Booysen, Elzaan; van Zyl, Leonardo; Trindade, Marla (Frontiers in Bioengineering and Biotechnology, 2023)
Biofilms are bacterial communities embedded in exopolymeric substances that form on the surfaces of both man-made and natural structures. Biofilm formation in industrial water systems such as cooling towers results in biofouling and biocorrosion and poses a major health concern as well as an economic burden. Traditionally, biofilms in industrial water systems are treated with alternating doses of oxidizing and non-oxidizing biocides, but as resistance increases, higher biocide concentrations are needed. Using chemically synthesized surfactants in combination with biocides is also not a new idea; however, these surfactants are often not biodegradable and lead to accumulation in natural water reservoirs. Biosurfactants have become an essential bioeconomy product for diverse applications; however, reports of their use in combating biofilm-related problems in water management systems is limited to only a few studies. Biosurfactants are powerful anti-biofilm agents and can act as biocides as well as biodispersants. In laboratory settings, the efficacy of biosurfactants as anti-biofilm agents can range between 26% and 99.8%. For example, long-chain rhamnolipids isolated from Burkholderia thailandensis inhibit biofilm formation between 50% and 90%, while a lipopeptide biosurfactant from Bacillus amyloliquefaciens was able to inhibit up to 96% and 99% biofilms. Additionally, biosurfactants can disperse preformed biofilms up to 95.9%. The efficacy of antibiotics can also be increased by between 25% and 50% when combined with biosurfactants, as seen for the V9T14 biosurfactant coformulated with ampicillin, cefazolin, and tobramycin. In this review, we discuss how biofilms are formed and if biosurfactants, as anti-biofilm agents, have a future in industrial water systems. We then summarize the reported mode of action for biosurfactant molecules and their functionality as biofilm dispersal agents. Finally, we highlight the application of biosurfactants in industrial water systems as anti-fouling and anti-corrosion agents.